Colaspis caligula, a new species found in association with Vitis vinifera (L.) crops in Argentina (Coleoptera: Chrysomelidae) - Agrain, Federico A.; Cabrera, Nora; Holgado, Miriam G.; Vicchi, Franco R. (Zootaxa, 2016)
Some species of Colaspis Fabricius are well-known pests of several crops in Argentina. In this contribution, we describe a new species within this genus: Colaspis caligula n. sp., found in association with Vitis vinifera (Linnaeus) crops. We provide descriptions and illustrations of the mature larva, pupa and adult, as well as notes on its diagnostic characters, life cycle, and the damages produced to the plants.